The Influence Of Borrower Characteristics, Income, And Business Type On The Level Of Smoothness In Return Of People's Business Credit (KUR) (Case Study at Bank BTN KCP Jombang in 2024) - Putra, Hasannudin Nursalim; Fuzaki, Alfani Amar; Metyopandi, Vierkury; Efionita, Yolanda; Amin, Rofikul (Business Management Research, 2026)
Micro, Small, and Medium Enterprises (MSMEs) serve as the vital backbone of the Indonesian economy, yet they frequently encounter structural hurdles in capital access and business management. To bridge this gap, the People's Business Credit (KUR) provides essential financing for feasible but non-bankable businesses. This research evaluates the critical factors determining the success of the KUR program, specifically focusing on the influence of borrower characteristics, income levels, and business types on repayment smoothness. Situated as a case study at Bank BTN KCP Jombang in 2024, the study addresses persistent challenges in loan installments despite existing government guarantees. Utilizing a quantitative approach, primary data were gathered from 30 KUR debtors selected through purposive sampling and analyzed via multiple linear regression. Empirical results reveal that all three variables significantly impact credit repayment. Notably, borrower characteristics exhibit a significant yet negative influence (sig = 0.021), suggesting that certain personal traits or high social responsibilities may inadvertently burden financial discipline. Conversely, income (sig = 0.000) and business type (sig = 0.000) demonstrate strong positive correlations with repayment performance. The model achieved an Adjusted R-Square of 0.961, indicating that 96.1% of the variance in repayment is explained by these factors. These findings highlight that while individual character is essential, the economic viability of the business sector and stable revenue streams are the primary drivers of credit quality.